Assistance for Today's Mothers for Teenagers in the Digital Age in Blendongan Hamlet, Sidoluhur Village - Diah Retno Ningsih; Fadilatul Rizky Maulida (Indonesian Journal of Society Development, 2023)
The assistance carried out in B;endongan Hamlet aims to ensure that mothers in Blendongan Hamlet who have teenage children can be more sensitive to changing times and also so that Blendong Hamlet mothers have an active role in the lives of their children in the Digital Era. The activities were carried out using two methods, namely lectures/presentation of material and small group discussions focusing on the problems experienced and their solutions. This mentoring was carried out for 6 months from March to August 2023. The results of the mentoring show a change in the mothers' mindset which is more towards the present in accordance with current conditions